Production of carbon-containing pyrite spherules induced by hyperthermophilic Thermococcales: a biosignature? - Truong, Chloé; Bernard, Sylvain; Le Pape, Pierre; Morin, Guillaume; Baya, Camille; Merrot, Pauline; Gorlas, Aurore; Guyot, François (Frontiers in Microbiology, 2023)
Thermococcales, a major order of hyperthermophilic archaea inhabiting iron- and sulfur-rich anaerobic parts of hydrothermal deep-sea vents, are known to induce the formation of iron phosphates, greigite (Fe3S4) and abundant quantities of pyrite (FeS2), including pyrite spherules. In the present study, we report the characterization of the sulfide and phosphate minerals produced in the presence of Thermococcales using X-Ray diffraction, synchrotron-based X ray absorption spectroscopy and scanning and transmission electron microscopies. Mixed valence Fe(II)-Fe(III) phosphates are interpreted as resulting from the activity of Thermococcales controlling phosphorus–iron–sulfur dynamics. The pyrite spherules (absent in abiotic control) consist of an assemblage of ultra-small nanocrystals of a few ten nanometers in size, showing coherently diffracting domain sizes of few nanometers. The production of these spherules occurs via a sulfur redox swing from S0 to S-2 and then to S-1, involving a comproportionation of (-II) and (0) oxidation states of sulfur, as supported by S-XANES data. Importantly, these pyrite spherules sequester biogenic organic compounds in small but detectable quantities, possibly making them good biosignatures to be searched for in extreme environments.